Pengembangan Bahan Ajar Teks Prosedur Berbasis Video Animasi Kelas VII SMP Muhammadiyah 03 Medan - Raisa Fadhilah Rangkuti; Abdurahman Adisaputera (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Evaluate the steps taken to create animated video-based teaching materials for procedural text, create an animated videos based teaching material for procedure text, and assess whether animation-based procedural texts are worthy of use in class VII in Muhammadiyah 03 Fields. This research is a developmental research with Borg and Gall designs. Data collection techniques implemented are structured interviews and rackets that will be given to students, teachers and experts. Descriptive analysis is the data analysis technique used in this research. The results of this study show that the results of validation by material experts, media experts, Indonesian language teachers, and student evaluation of the materials developed indicate that the materials are in the category of "Very Worthy". The validation results of the qualification can be described as follows: 88% of the evaluation results are very good, 2% of the media results are good, 91% of the lesson outcome is good, and 93% of the student or student participant's credibility is good.